Preparation of an Encapsulated Seed for the Preservation of Aquilaria malaccensis Seed - Kharnaior, Suklang; Thomas, Shiny C. (Indian Forester, 2024)
The main objective of the study is to understand the seed viability of Aquilaria malaccensis using 2,3,5 tetrazolium chloride (TTC) based assays and trypan blue. The effects of storage of encapsulated and non-encapsulated seeds stored for 0, 15, and 30 days were also studied. After storing the samples were stained with 2,3,5 tetrazolium chloride assays and trypan blue. It was found that the encapsulated seeds (4 % sodium alginate) stored at 4° C and 25° C for 15 and 30 days show a high potential in terms of viability compared to the seed encapsulated with 6% sodium alginate and un-encapsulated seeds. It was also observed that the non-encapsulated seeds stored at 4° C revealed high viability compared to seeds stored at 25° C. Tetrazolium chloride assay is more accurate and stable for seed viability compared to trypan blue assay. However, it was found that encapsulation and temperature play a vital role in maintaining the viability of the seeds. Hence this technique can be used for the conservation, maintenance, and regeneration of A. malaccensis and various species through seed encapsulation.